Factors influencing return for maintenance treatment with percutaneous tibial nerve stimulation for the management of the overactive bladder. (3rd February 2019) - Salatzki, Janek; Liechti, Martina D.; Spanudakis, Eleonora; Gonzales, Gwen; Baldwin, Joanne; Haslam, Collette; Pakzad, Mahreen; Panicker, Jalesh N.
Abstract : Objectives: To identify factors influencing return for maintenance percutaneous tibial nerve stimulation (PTNS) treatment after successful completion of a 12‐week course of treatment for overactive bladder (OAB). Patients and Methods: Patients with OAB symptoms referred for PTNS treatment underwent 12 sessions of weekly PTNS treatment and were evaluated at baseline and week 12 using the International Consultation on Incontinence Questionnaire on OAB, the International Consultation on Incontinence Questionnaire on lower urinary tract symptom‐related quality of life (ICIQ‐LUTSqol) and a bladder diary (BD). Responders to treatment, evaluated using two patient‐reported outcome measures, were invited to return for maintenance treatment when symptoms returned. A PTNS Service Evaluation Questionnaire was used to evaluate factors influencing return for maintenance treatment. Results: Seventy‐three patients were evaluated (mean age 58.9 [±14.7] years, 72.6% women) and clustered into three groups: group 1 ( n = 25) did not respond to 12 weekly sessions of PTNS treatment; group 2 ( n = 17) responded to treatment but did not return for maintenance treatment and group 3 ( n = 31) responded to treatment and returned for maintenance treatment. There were no significant differences in demographic characteristics, diagnosis, baseline symptom scores and BD variables among the three groups. Patients belonging to groups 2 and 3 experienced a significant improvement from baseline to week 12 in total OAB scores (group 2: −1.54 ± 1.85; group 3: −1.85 ± 2.28; P < 0.05); however, patients returning for maintenance treatment reported significant improvements specifically in nocturia (BD difference = −0.4 ± 0.7 [ P < 0.05] and ICIQ‐LUTSqol difference −0.48 ± 0.94 [ P < 0.05]), and perceived benefits of the treatment with regard to their OAB symptoms compared to those not returning for maintenance treatment (difference between the two groups 25.6%; P = 0.030). Improvements in nocturia and perceived benefits predicted return for maintenance treatment based on a logistic regression analysis. Factors related to the need for repeat clinic visits, such as transportation, distance and time commitment, were not found to differ between the two groups. Conclusions: Twelve‐session weekly PTNS is a safe and effective treatment for OAB. Responders to treatment returning for maintenance PTNS more often reported significant improvements in nocturia and perceived benefits over time, compared to those not returning for maintenance treatment. The BD provides a more objective assessment of treatment outcome after PTNS treatment.